Labour - Florence, P. Sargant (Philip Sargant), 1890-1982 (Routledge library editions. Economics series., 2003)
Labour focuses on the issues and problems concerning the efficient full employment of labour in a free market economy. The discussion is largely about the conditions (including comparative wages) underlying industrial efficiency and maximum production from various labour resources at least cost. By estimating man-power, analysing the human factor and measuring labour efficiency, the book summarizes recent evidence on employment conditions for or against efficiency and the effect upon the incidence of unemployment.